Analysis of E-CRM and e-Service Quality of Customer Loyalty at PT. Kidang Rangga Jakarta Mebel With Satisfaction as a Intervening Variable: Analysis of E-CRM and e-Service Quality of Customer Loyalty at PT. Kidang Rangga Jakarta Mebel With Satisfaction as a Intervening Variable - Tubagus Ahmad Darojat (Jurnal Mantik, 2020)
Research objectives to test the influence of E-CRM and e-service quality against customer loyalty with satisfaction as a intervening variable. The research object is the customer PT. Kidang Rangga Mebel Jakarta with a sample of 160 customers. Types of quantitative research by spreading questionnaires. The method of research path analysis with the analysis tool is SEM with the help of Amos version 20.0. It was found that e-CRM and e-service quality have positive and significant impact on customer satisfaction and loyalty of PT. Kidang Rangga Mebel Jakarta. Satisfaction positively and significantly influence the customer loyalty of PT. Kidang Rangga Mebel Jakarta. Contentment of partial mediation the influence of E-CRM and e-service quality to customer loyalty PT. Kidang Rangga Mebel Jakarta.